Bursa omentalis - Smerdu, Vika (Medicinski razgledi, 2008)
Bursa omentalis (lesser sac) is a vertical peritoneal cavity behind the stomach. It communicates with the main peritoneal cavity (greater sac) throughthe foramen omentale, an opening located under the liver and posterior to the hepatoduodenal ligament. The anterior wall of the omental bursa is formed by the stomach and its double-layered peritoneal folds. The fold extending from the lesser curvature of the stomach and the superior part of the duodenum to the liver is called the lesser omentum (lat. omentum minus). Apart from this, another fold extends from the greater curvature to the diaphragm as the gastrophrenic ligament, to the left towards the spleen as thegastrosplenic ligament, and downwards to the transverse colon as the gastrocolic ligament. The posterior wall of the omental bursa is formed mainlyby the parietal peritoneum, which covers the diaphragm, the aorta and its branches, the pancreas, the upper pole of the left kidney and the left suprarenal gland. (Abstract truncated at 2000 characters)
Keywords: Omentum; Peritoneal Cavity; Peritonealna votlina; Anatomy And Histology; bursa omentalis; anatomija; histologija; kirurško zdravljenje